2013
DOI: 10.1007/s13205-013-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Ficus religiosa L. via leaf explants and comparative evaluation of acetylcholinesterase inhibitory activity in the micropropagated and conventionally grown plants

Abstract: A high-frequency, season-independent, in vitro regeneration of Ficusreligiosa was developed, followed by comparative acetylcholinesterase inhibitory (AChEI) activity assay of the in vitro raised and conventionally grown plants. The use of AChEI activity is the most accepted strategy for the treatment of Alzheimer disease. Fully expanded, mature leaves were cut into different segments to initiate the cultures. The middle section of the leaf in vertical orientation with cut portion inserted inside the medium was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
4
13
1
Order By: Relevance
“…Many studies proved the positive influence of cytokinin on cell division and shoot regeneration (Arab et al, 2014;Jafari et al, 2017;Gill, 2011, 2014). Hesami et al (2017a) and Siwach and Gill (2014) reported that TDZ is more effective than BAP on the number of shoot regeneration, whereas various studies take a radical point of view and alleged that BAP is more effective than TDZ (Deshpande et al, 1998;Hassan et al, 2009;. Therefore, these conflicting results might be related to the use of various explants and effects of various genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies proved the positive influence of cytokinin on cell division and shoot regeneration (Arab et al, 2014;Jafari et al, 2017;Gill, 2011, 2014). Hesami et al (2017a) and Siwach and Gill (2014) reported that TDZ is more effective than BAP on the number of shoot regeneration, whereas various studies take a radical point of view and alleged that BAP is more effective than TDZ (Deshpande et al, 1998;Hassan et al, 2009;. Therefore, these conflicting results might be related to the use of various explants and effects of various genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, reported that the maximum number of multiple shoots from nodal segments of F. religiosa was achieved on WPM containing 1.0 mg · L -1 BAP along with 0.5 mg · L -1 IAA, and these findings confirmed our results. The influence of cytokinins on micropropagation can be varied based on the kind of culture medium, the variety of plants, and the age of explants (Bhojwani and Dantu, 2013;Hesami et al, 2017b;Siwach and Gill, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and Hesami et al (2017c) reported that 2 mg/l IBA and 0.1 mg/l NAA were suitable for inducing the rooting of F. religiosa. Siwach and Gill (2011) and Siwach and Gill (2014) also reported that IBA was more appropriate than NAA and IAA in inducing the rooting process in F. religiosa. IBA is more stable and less sensitive to degradation and is slowly metabolized by the peroxidase enzyme; this can be one of the possible causes for better effect of IBA in root formation as compared to other auxins (Dobránszki and da Silva, 2010).…”
Section: Effect Of Iba or Naa On Root Formationmentioning
confidence: 93%